Antarctophthirus carlinii (Anoplura: Echinophthiriidae), a new species from the Weddell seal Leptonychotes weddelli - Leonardi, María Soledad; Poljak, Sebastián; Carlini, Pedro; Galliari, Juan; Bobinac, Magali; Santos, Mercedes; Márquez, María E.; Negrete, Javier (Parasitology Research)
As a part of an ongoing long-term study on the biology of pack-ice seals in Antarctica, we had the opportunity to collect lice from Weddell seals (Leptonychotes weddelli). We did not find the original description of this host-parasite association. Antarctophthirus ogmorhini had previously been reported as a parasite for the Weddell seal, but the information is, to a certain extent, confusing. During the development of the present study, we had access to literature concerning the presence of A. ogmorhini on this host, which, to our knowledge, was not determined in any of the previous works on this species. We compared lice collected from Weddell seals with A. ogmorhini obtained from the type host, the leopard seal (Hydrurga leptonyx), and we found that both species can be distinguished. The main differences are the characteristic pattern of chaetotaxy in the dorsal side of the head in lice from Weddell seals, the size and form of the pseudopenis, and the distribution and size of the fringe of setae surrounding the genital opening. Considering the conservative morphology, and ecological and evolutionary features of sucking lice, we proposed that lice from Weddell seals constitute a new species. In the present work, we described and illustrated adults of this new species collected from Weddell seals during the austral summer of 2014 at the Danco Coast, Antarctic Peninsula. Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Poljak, Sebastián. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Cordoba. Instituto de Diversidad y Ecologia Animal; Argentina Fil: Carlini, Pedro. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Galliari, Juan. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Bobinac, Magali. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque ...